Bibliometric Mapping of WhatsApp-Based Health Research (2015–2025): Global Trends, Leading Countries, and Emerging Themes - Intan Gumilang Pratiwi; E.W.N Sofianto; Baiq Yuni Fitri Hamidiyanti; Ati Sulianty; Margareta Melani; Qorinah Estiningtyas Sakilah Adnani (Direktorat Politeknik Kesehatan Makassar, 2025)
The use of WhatsApp (WA) in the health sector is increasingly widespread for communication, education, and intervention. Yet, systematic and updated bibliometric analyses of global trends remain limited, particularly those covering post-2023 developments and comparing contributions between high-income and developing countries. This study aims to systematically map and analyze the international landscape of WA-based health research published between 2015 and 2025. We employed a bibliometric research design with data sourced from the Scopus database, using the keywords